Dinamika Kesiapan Pedagogis Guru dalam Integrasi Artificial Intelligence (AI) pada Pembelajaran Sekolah Menengah Atas - Dewi Saputri; Rilma Maya Dela (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
This study aims to explore the dynamics of teachers’ pedagogical readiness in utilizing Artificial Intelligence (AI) in learning at SMA Negeri 2 Singkawang. The study employed a qualitative descriptive approach to understand teachers’ experiences, perceptions, strategies, and challenges in integrating AI into the learning process. The participants consisted of six teachers selected purposively based on their experience in using AI in teaching activities. Data were collected through semi-structured interviews and documentation. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that teachers have begun utilizing AI in various learning activities, such as preparing teaching materials, designing assessments, visualizing abstract concepts, and creating more interactive learning experiences. The use of AI has also encouraged changes in teachers’ instructional practices, where teachers increasingly act as facilitators who guide students in using technology critically and responsibly. However, several challenges were identified, including students’ dependence on AI, the risk of biased and inaccurate information, reduced critical thinking skills, and difficulties in maintaining authentic learning experiences. These findings imply that strengthening teachers' pedagogical readiness should become a key consideration in supporting the effective and responsible integration of Artificial Intelligence (AI) in learning.